'The bike breaks down. What are they going to do?' Actor-networks and the Bicycles for Development movement. (March 2021) - McSweeney, Mitchell; Millington, Brad; Hayhurst, Lyndsay; Wilson, Brian; Ardizzi, Madison; Otte, Janet
This article reports on an empirical study of 'Bicycles for Development' (BFD) – a nascent movement whereby used bicycles are collected (often in the global North) and distributed in development contexts (often in the global South) with the aim of achieving a range of positive social outcomes (e.g. access to education). Drawing from interviews ( n = 32) with participants from 19 BFD organizations, and informed by actor-network theory (ANT), the analysis presented herein specifically highlights three key factors that facilitate and/or hinder BFD work: (a) government regulations that potentially stem or ease the flow of bicycles into development contexts; (b) the bicycle's material constitution, and specifically its sturdiness (or lack thereof); and (c) environmental conditions that impact how bicycles are made, distributed and used. A key theme that cuts across these findings is the potential for non-humans to cause 'frictions' that potentially disrupt, divert, but also help in realizing the programmes of action of BFD organizations. We consider the relevance of these findings for both the BFD movement in particular and the wider Sport for Development and Peace (SDP) movement in general. Based on study findings, we argue for ANT as a useful framework for achieving a widened analytical focus and thus for delivering more robust accounts of development contexts under study.